The Effect of the Application of Discovery Learning and Problem Based Learning Model on Metacognitive Ability and Students' Mathematical Connections - Rini Triana; Zainal Azis; Irvan Irvan (UMSU, 2021)
This study aims to determine: (1) the significant influence between learning models on metacognitive abilities, (2) significant effects between learning models on mathematical connections,(3) the interaction betweendiscovery learningandproblem based learningon metacognitive abilities, (4) the interaction betweendiscovery learningandproblem based learningmodelson students' mathematical connections.This research is aquasi experimentalresearch.The instruments used were: (1) tests of students 'initial mathematical abilities (2) tests of metacognitive abilities, (3) tests of students' mathematical connections with the subject of Lines and Angles.Inferential data were performed using covariance analysis (MANOVA).Theresult of hypothesis testingshows thatthe average metacognitive ability in learning usingdiscovery learninglearning modelsis 77.20 75 with a standard deviation of 2.161 and students' mathematical connections obtained are 83.63 45 with a standard deviation of 3.480.Byusing theproblem base learningmodelis 76.76 75 with a standard deviation of 2.216 and for the average mathematical connection of the students obtained 81.8445with a standard deviation of 2.096.The data show thatthe metacognitive abilities and mathematical connections of students who are taught usingdiscoverylearning modelsare better thanthose who are taught usingproblem-based learningmodels